Reproductive features of the deep-water rose shrimp, Parapenaeus longirostris (Crustacea: Penaeidae), in the Strait of Sicily - BIANCHINI, M.L.; DI STEFANO, L.; RAGONESE, S. (Mediterranean Marine Science, 2010)
The deep‑water rose shrimp, Parapenaeus longirostris (Lucas, 1846), is one of the most valuable and heavily exploited demersal species of the Mediterranean bottom trawl fisheries. The basic life traits of this shrimp, in particular its reproductive aspects, are regularly monitored during experimental trawl surveys carried out in the Mediterranean Sea. Gonadic condition and maturity status for estimating the size at onset of sexual maturity are commonly assessed in females, using macroscopic color scales, histologically validated only in a few geographical areas. In this study, histological analyses were performed on rose shrimps collected from a trawl survey carried out in the Strait of Sicily, in order to support the empirical 4‑stage macroscopic scale locally employed. Ovaries from females of different sizes, ranging between 16 mm and 40 mm carapace length, were collected and used for microscopic examination of their structure, for oocytes counts and for oocyte diameter frequency distributions; oocytes diameter was measured by imaging analysis. The collected data were also used to estimate other basic vital parameters of the rose shrimp population. The histological observations show a broad correspondence between ovarian development and macroscopic features; therefore, the classifications derived by the empirical scale remain suitable for estimating the maturity parameters.